2021
DOI: 10.1002/tox.23118
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐chronic exposure to ammonia inhibits the growth of juvenile Wuchang bream (Megalobrama amblycephala) mainly by downregulation of growth hormone/insulin‐like growth factor axis

Abstract: In this study, healthy Wuchang bream (Megalobrama amblycephala) juveniles were exposed to 0, 5, 10, 20 and 30 mg/L total ammonia nitrogen for 30 days to elucidate toxic effects and mechanisms of ammonia on growth performance involved with the regulation of growth hormone/insulin-like growth factor (GH/IGF) and hypothalamic-pituitary-thyroid (HPT) axes. Our results showed that the increasing total ammonia nitrogen concentrations caused dose-depend decreases in the weight gain and specific growth rate but increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 74 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…The present study showed that chronic ammonia exposure inhibited growth performance and reduced survival rate of juvenile oriental river prawns, similar to results in juvenile Wuchang bream (M. amblycephala) and juvenile yellow catfish. 30,31 However, ammonia did not affect growth performance in channel catfish (Ictalurus punctatus) and Senegalese sole (Solea senegalensis). 32,33 The discrepancy indicated that the tolerance to ammonia in aquatic animals is species specific.…”
Section: Discussionmentioning
confidence: 98%
“…The present study showed that chronic ammonia exposure inhibited growth performance and reduced survival rate of juvenile oriental river prawns, similar to results in juvenile Wuchang bream (M. amblycephala) and juvenile yellow catfish. 30,31 However, ammonia did not affect growth performance in channel catfish (Ictalurus punctatus) and Senegalese sole (Solea senegalensis). 32,33 The discrepancy indicated that the tolerance to ammonia in aquatic animals is species specific.…”
Section: Discussionmentioning
confidence: 98%
“…Traditional aquaculture, in which fish feces and feed residue could cause water eutrophication, is not regarded as an eco‐friendly model. With the release of ammonia from fish feces and feed residue into the water environment, ammonia toxicity may limit the growth of bream by modulating growth hormone/insulin‐like growth factor and hypothalamic–pituitary–thyroid axes 46 . Also, ammonia stress has negative effects on the antioxidant capacity and livability of aquatic animals 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The blunt snout bream (Megalobrama amblycephala) is a widely distributed and commercially important aquaculture species in China. M. amblycephala is strongly responsive to biotic and abiotic stressors, including Aeromonas hydrophila and Cd, which threatens its culture industry and causes huge economic losses [26,27]. Research into its mechanism of innate immunity to defense pathogens and anti-environment stress is becoming an urgent task that will benefit and improve the immunity of fish in the future.…”
Section: Introductionmentioning
confidence: 99%